PEER TUTORING IN LEARNING A FOREIGN LANGUAGE AS A NON-MAJOR - E. A. Makarova (Образование и наука)
Introduction. The problems of stimulation cognitive activity and improvement of student learning motivation are of interest for many Russian and foreign researchers. One of the approaches to solve these problems, actively implemented in educational process abroad, is peer tutoring. Peer tutoring is a form of collaborative learning based on the models of student interactions organized in pairs or groups with shared roles «peer tutor- tutee».The aim of the study is to analyze effective models of peer tutoring used abroad, to develop alternate models and apply them while teaching reading and translation at foreign language lessons in non-linguistic university.Methodology and research methods. Peer tutoring is studied by using both qualitative and quantitative research methods such as data collection, analysis and generalizations along with the experiment and observation.Results and scientific novelty. As a result the peer tutoring models have been developed and implemented within the regular classroom settings while teaching reading and translation to students in non-linguistic university. The offered models of tutoring involve preparation realities of the Russian higher education institutions; meanwhile, there are no special centers of mentoring with separate teaching staff and psychologists in foreign universities. The advantages of peer tutoring over traditional forms of education and a group form of work when students solve a problem are designated, but their roles are not accurately distributed. The undertaken experiment lasted for two years, showed that peer tutoring advantages in foreign language training consist in the following: firstly, such way of lessons allows teachers to avoid time-losing monotonous reading and translations of texts discouraging students; secondly, exchanging opinions, students study each other and gain skills of estimation of personal and others' work; thirdly, interacting in pairs or small groups, pupils are more active, than during the independent work or work organized by the teacher, they react to the arising educational situations; finally, such training considerably solves a problem of shortage of class periods on teaching the subject "Foreign language" as students manage to cope with much large scope of a training material as compared they manage to make during the traditional organization of an educational process.Practical significance. The obtained data contribute to the study of educational problems of adaptation and motivation, and can be used in teaching foreign languages as well as major subjects at higher educational institutions.